Grasping and Manipulation: Neural Bases and Anatomical Circuitry in Humans. (15th March 2021) - Errante, Antonino; Ziccarelli, Settimio; Mingolla, Gloria; Fogassi, Leonardo
Highlights: Grasping actions require the integration of visual information and motor signals. Grasping activates both dorso-dorsal and dorso-ventral parieto-frontal circuits. Manipulative actions are based on somatomotor transformations. Manipulation relies on partially segregated functional circuits with respect to grasping. Both grasping and manipulation involve basal ganglia and cerebellum. Abstract: Neurophysiological and neuroimaging evidence suggests a significant contribution of several brain areas, including subdivisions of the parietal and the premotor cortex, during the processing of different components of hand and arm movements. Many investigations improved our knowledge about the neural processes underlying the execution of reaching and grasping actions, while few studies have directly investigated object manipulation. Most studies on the latter topic concern the use of tools to achieve specific goals. Yet, there are very few studies on pure manipulation performed in order to explore and recognize objects, as well as on manipulation performed with a high level of manual dexterity. Another dimension that is quite neglected by the available studies on grasping and manipulation is, on the one hand, the contribution of the subcortical nodes, first of all the basal ganglia and cerebellum, to these functions, and, on the other hand, recurrent connections of these structures with cortical areas. In the first part, we have reviewed the parieto-premotor and subcortical circuits underlying reaching and grasping in humans, with a focus on functional neuroimaging data. Then, we have described the main structures recruited during object manipulation. We have also reported the contribution of recent structural connectivity techniques whereby the cortico-cortical and cortico-subcortical connections of grasping-related and manipulation-related areas in the human brain can be determined. Based on our review, we have concluded that studies on cortical and subcortical circuits involved in grasping and manipulation might be promising to provide new insights about motor learning and brain plasticity in patients with motor disorders.